2016
DOI: 10.1002/app.43539
|View full text |Cite
|
Sign up to set email alerts
|

The effect of UV irradiation on the electrospun PCL/TiO2 composites fibers

Abstract: The effect of UV irradiation and micro‐ and nano‐TiO2 as well as titanate nanotubes (TiNT) on the phase morphology and thermal properties of the electrospun PCL composite fibers was investigated. Polycaprolactone (PCL)/TiO2 (micro‐ and nano‐TiO2 as well as titanate nanotubes) composite fibers were prepared by electrospinning a polymer solution. The PCL and PCL/TiO2 composite fibers were exposed to UV light at irradiation times of 5 and 10 days. After UV irradiation the crystallinity of the electrospun PCL/TiNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Anatase has proved the most efficient species in photocatalysis, because of its higher surface area and redox ability [26]. In tissue engineering, inorganic materials such as TiO 2 have shown excellent bacterial resistance and thermal stability over organic antibacterial materials [21,27,28,29,30,31,32,33]. Other systems studied with PCL as biopolymer for electrospinning are ZnO and Mg for their multifunctional properties, hydrophilicity and bioactivity, especially in terms of antibacterial activity [23,34].…”
Section: Introductionmentioning
confidence: 99%
“…Anatase has proved the most efficient species in photocatalysis, because of its higher surface area and redox ability [26]. In tissue engineering, inorganic materials such as TiO 2 have shown excellent bacterial resistance and thermal stability over organic antibacterial materials [21,27,28,29,30,31,32,33]. Other systems studied with PCL as biopolymer for electrospinning are ZnO and Mg for their multifunctional properties, hydrophilicity and bioactivity, especially in terms of antibacterial activity [23,34].…”
Section: Introductionmentioning
confidence: 99%
“…In many organic aprotic solvents, however, such a mechanism of stabilization does not occur. Recently, we have found that CTAB coated TiNT can be suspended in polar aprotic solvents (chloroform) by long term stirring . FTIR spectra (Figure ) indicate the strong adsorption of CTAB on the surface of nanotubes, probably due to interaction between OH groups in TiNT and  NR4+ groups in CTAB.…”
Section: Resultsmentioning
confidence: 98%
“…Using our previously established method of untangle nanotubes agglomerates without shortening of their length by long term stirring, the colloidal solution of isolated TiNT obtained by 2 weeks stirring was used for preparation of PI/TiNT composite nanofibers. Figure (c,d) shows TEM image of polyimide nanofibers reinforced by titanate nanotubes prepared by ex situ and in situ respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually the fiber diameter ranges from a few nanometers to a few micrometers. [4][5][6] Electrospun drug loaded fibers have been widely explored for targeted release, for improving the dissolution rate of poorly water-soluble drugs, and for encapsulating multiple functional components. [7][8][9][10] However, when fabricating nanofibers a burst release of drug is often observed even if the polymer filament is insoluble in water (as is the case for PCL).…”
Section: Introductionmentioning
confidence: 99%